Activation of metabotropic glutamate (mGlu)2 receptors suppresses histamine release in limbic brain regions following acute ketamine challenge - Fell, Matthew J.; Katner, Jason S.; Johnson, Bryan G.; Khilevich, Albert; Schkeryantz, Jeffrey M.; Perry, Kenneth W.; Svensson, Kjell A. (Neuropharmacology, 2010)
In the present study we demonstrated that ketamine, an NMDA antagonist and possible psychotomimetic, increases extracellular histamine (HA) in the rat brain. We then examined the ability of the group II mGlu receptor agonist LY379268 to modulate the ketamine evoked increases in HA release in three limbic brain regions. Ketamine (25 mg/kg) increased HA in the medial prefrontal cortex (mPFC), ventral hippocampus (vHipp) and the nucleus accumbens (NAc) shell. LY379268 administered alone was without effect on basal HA efflux in the mPFC or vHipp but modestly decreased HA efflux in the NAc shell. Administration of LY379268 (3 and 10 mg/kg) prior to ketamine significantly attenuated the HA response in the mPFC, vHipp and the NAc shell. The inhibitory effects of LY379268 in the mPFC were mimicked by the systemic administration of the mGlu2 receptor positive allosteric modulator CBiPES (60 mg/kg). Finally, local perfusion experiments revealed that the effects of LY379268 on ketamine evoked HA efflux appear to be mediated by mGlu2 receptors outside the PFC as the intra-mPFC perfusion of LY379268 (100 μM or 300 μM) failed to attenuate ketamine evoked increases in HA efflux. Together, these novel observations reveal an effect of ketamine on histaminergic transmission in limbic brain areas and provide further insight into the possible antipsychotic mechanism of action of mGlu2/3 receptor agonists.